2000
DOI: 10.1063/1.125718
|View full text |Cite
|
Sign up to set email alerts
|

Efficient GaAs light-emitting diodes by photon recycling

Abstract: Heterostructure AlGaAs/GaAs light-emitting diodes (LEDs) with a thick active region have shown high external efficiencies, thanks to reabsorption in the active region. For high injection currents and low temperature, we report a 22% efficiency which corresponds to a 98% efficiency internally. We discuss the application of such LED when integrated with a quantum-well infrared photodetector for pixelless thermal imaging systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 10 publications
0
32
0
Order By: Relevance
“…The long integration times can be shortened by two or three orders of magnitude if we join the QWIPLED device to the CCD array via a fiber bundle. Another order magnitude could probably be obtained by implementing our results on optimum gratings, since a higher BLIP temperature would allow to bias the device more, and by using photon recycling effects in the LED active region [11].…”
Section: Discussionmentioning
confidence: 98%
“…The long integration times can be shortened by two or three orders of magnitude if we join the QWIPLED device to the CCD array via a fiber bundle. Another order magnitude could probably be obtained by implementing our results on optimum gratings, since a higher BLIP temperature would allow to bias the device more, and by using photon recycling effects in the LED active region [11].…”
Section: Discussionmentioning
confidence: 98%
“…The relatively low external up-conversion efficiency is mainly due to the very small escape probability (~2%) of photons from the flat topsurface LED. This could be significantly improved via photon recycling and various other methods [15,22]. The optical up-conversion devices can be used to make low-cost mid-infrared imaging cameras.…”
Section: Resultsmentioning
confidence: 98%
“…On the LED side, the maximum external efficiency for a flat top-surface GaAs/AlGaAs LED was calculated to be ~0.02 W/A if excluding any photon recycling effect [21]. The measured LED external efficiency is apparently greater than this theoretical limit when biased above 1.97 V. This denotes that the photon recycling effect was playing a critical role in enhancing the extraction efficiency of the photons generated in the LED part and thence the external efficiency [22]. It has been shown that with optimized photon recycling designs for layer structure, the external efficiency of a flat topsurface LED could be improved to ~ 0.1 W/A [21].…”
Section: (B) (A)mentioning
confidence: 99%
“…Due to the large refractive index of the semiconductor, most light generated inside the LED was totally reflected at the semiconductor/air interface and only 2% of the light came out. The extraction efficiency can be considerably improved using a number of techniques, including photon recycling [10], a resonant cavity LED structure [11], and textured surface scattering [12]. Another reason for the low efficiency is the low LED internal quantum efficiency, caused by small barrier height and poor carrier confinement in the InP material system.…”
Section: Resultsmentioning
confidence: 99%